Pengaruh Sertifikasi Kakao terhadap Penurunan Praktik Perbudakan Anak oleh Petani Kakao di Pantai Gading - Azzahra Soraya Bilhaq; Fendy Eko Wahyudi; Shary Charlotte Pattipelohy (Journal of International Relations Diponegoro, 2018)
Ivory Coast is the largest cocoa producer in the world, but in the process of production there are child labour incident that occur due to several factors. Children under the age of 17 do work like cutting cocoa beans using a machete or a large knife in Ivory Coast's cocoa plantation. Some of the child laborers in Ivory Coast are a victims of human smuggling and come from neighboring countries such as Ghana, Burkina Faso and Mali. Child slavery is an act that violates the rights of children and adversely affects the child's physical, mental, and future. Cocoa certification is a way to ensure the quality of cocoa plantation production. This research using descriptive-analytic method with neoliberalism perpective to approach the issue. International relations is important in order to find a solution. UTZ Certified has a sustainable program that is followed by cocoa farmers in Ivory Coast and in the program the problem of child labour is also a matter of concern. UTZ Certified as non-profit international organization works with communities, international organizations and chocolate companies to reduce the practice of child slavery in Ivory Coast.